2007
DOI: 10.3354/ame01139
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dynamics in autotrophic and heterotrophic seawater mesocosms. II. Bacterioplankton community structure and hydrolytic enzyme activities

Abstract: A 20 d seawater mesocosm experiment was conducted to study microbial loop and carbon cycling dynamics in 3 experimental systems of different trophic status. Two mesocosms were supplemented with phytoplankton (Phaeocystis in one mesocosm and diatoms in another). This report details the variations in bacterial community composition and in carbon utilization potential investigated via assays measuring the hydrolysis of complex polysaccharides and a simple peptide compound. The first half of the study period was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 70 publications
6
32
0
Order By: Relevance
“…High levels of dissolved endopeptidase activity in coastal seawater (Obayashi and Suzuki, 2008) also underscore the importance of cell-free enzymes in the ocean. The relative contributions of cell-free enzymes to total hydrolytic activity varies among enzymes; for example, contributions of dissolved laminarinase and xylanase to total hydrolytic activities were found to vary with site and season in a riverine-marine transect (Keith and Arnosti, 2001), and varied temporally during the course of a mesocosm bloom (Murray et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of dissolved endopeptidase activity in coastal seawater (Obayashi and Suzuki, 2008) also underscore the importance of cell-free enzymes in the ocean. The relative contributions of cell-free enzymes to total hydrolytic activity varies among enzymes; for example, contributions of dissolved laminarinase and xylanase to total hydrolytic activities were found to vary with site and season in a riverine-marine transect (Keith and Arnosti, 2001), and varied temporally during the course of a mesocosm bloom (Murray et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sundh 1992, Giroldo et al 2007). Even so, it is not known which algal species are the major EPP producers, though tight species-specific algal-bacterial relationships have been suggested for naturally occurring bacterial-algal consortia (Lindström 2001, Grossart et al 2005, Murray et al 2007.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Lindström 2001, Grossart et al 2005, Murray et al 2007). In a study of 5 mesotrophic lakes in Sweden, bacterioplankton composition was found to be significantly related to the biomass of cryptophytes and diatoms; however, the mechanisms of such algal-bacterial interactions remained unexplained (Lindström 2000(Lindström , 2001.…”
Section: Impact Of Phytoplankton On Bacterioplankton Community Composmentioning
confidence: 99%
See 2 more Smart Citations